"Oral health as an important milieu for social and mental health": Perspectives of adolescents emerging from a qualitative study - Folake Barakat Lawal; Folake Barakat Lawal; Omotayo Francis Fagbule; Taiwo Akeem Lawal; Gbemisola Aderemi Oke (Frontiers Media S.A., 2022)
BackgroundRecent evidence showed that the prevalence of oral diseases is still high among adolescents in many developing countries, including Nigeria. It therefore has becomes pertinent to focus on appropriate oral health interventions to promote oral health among them. This necessitates investigating the perspectives of adolescents, who are the major stakeholders, on the importance of oral health as baseline data needed in planning appropriate primary interventions.AimThe aim of the study was to explore the perspectives of adolescents on the importance of oral health.MethodsAn explorative qualitative study was conducted among adolescents attending senior secondary school I (grade 10) in the metropolis of Ibadan, Nigeria. A total of 12 focus group discussions were conducted among 120 adolescents aged 14 to 19 years. The discussions were transcribed verbatim, and triangulation and organization, as well as thematic analysis, of data were carried out.ResultsSome adolescents had positive perceptions of oral health and valued it as highly important, although some had contrary views and believed oral health was unimportant. Oral health is described as being integral to general health, is associated with eating and communication, is a means of survival and confidence building, and is a prelude to attract the opposite gender. Adolescents perceived the need for oral health education and dental treatment.ConclusionAdolescents have mixed perspectives on the importance of oral health; while some valued it as highly important, others believed it was of no significance. Those who valued oral health as important described it as a milieu for general health, human survival, and social and mental health and thus requested for oral health promotion in schools.